Characterization and Function of a Novel Welan Gum Lyase From Marine Sphingomonas sp. WG - Chang, Ai-Ping; Qian, Jin; Li, Hui; Wang, Ying-Lu; Lin, Jie-Ying; He, Qiao-Mei; Shen, Ya-Ling; Zhu, Hu (Frontiers in Microbiology, 2021)
Welan gum, a kind of microbial exopolysaccharides, produced by the genus Sphingomonas, have great potential for application in many fields, such as the food industry, cement production, and enhanced oil recovery. But there are still challenges to reduce the cost, enhance the production and the quality. Herein, the bioinformatics analysis of WelR gene was preformed, and the characterization and function of WelR, welan gum lyase, from Sphingomonas sp. WG were investigated for the first time. The results indicated that 382nd (Asn), 383rd (Met), 494th (Asn), and 568th (Glu) were the key amino acid residues, and C-terminal amino acids were essential to keeping the stability of WelR. The optimal temperature and pH of the enzymatic activity were found to be 25 °C and 7.4, respectively. And WelR was good low temperature resistance and alkali resistant. K+, Mg2+, Ca2+, Mn2+, and EDTA increased WelR activities, in contrast to Zn2+. Coupled with the change in glucose concentration and growth profile, the qRT-PCR results indicated that WelR may degrade welan gum existing in the culture to maintain bacterial metabolism when glucose was depleted. This work will lay a theoretical foundation to establish new strategies for the regulation of welan gum biosynthesis.